Distributive and Semantic Interpretation of Macedonian Pronominal Clitics: Three Cases - Karapejovski, Boban (“Dimitrie Cantemir” Christian University, Faculty of foreign languages and literatures, 2013)
The predominant linguistic concepts, traditional grammar and hitherto used description, have mostly focused on language per se. However, we will step out of the frames of this view and attempt to concentrate on three cases, which, being exceptions, may be interpreted from three different aspects, which are not necessarily mutually exclusive: a) as an interference within the Balkan Language Area; b) as a reflection of the way reality is perceived and an exception regarding the linguistic projection of this reality; c) as a linguistic marginal case, which (barely) exists in the Macedonian language and in the languages of some of the other Balkan dialects. We will look into three cases that focus on clitics: 1. the so-called “jumping clitics”; 2. a combination of dative and accusative forms; 3. the case whose paradigmatic properties are founded upon the example: “Kje ni svaram kafe/Will (to) us make coffee.” Since these cases stand out as exceptions from the predominant description in Macedonian, we will correlate them with the rest of the Balkan languages and raise them to the level of a new Balkan phenomenon, an expression of the common mentality. Or, on the other hand, we will discard them as a marginal case in linguistics.
Keywords: linguistics, traditional grammar, linguistic description, clitics, Balkan Language Area, Macedonian language, Balkan languages, exceptional grammatical forms